Molecular cloning and bioinformatics analysis of shrimp lvprofilin implicated in muscle formation and muscle specific gene regulation. - Laoong-u-thai, Yanisa
Shrimp is the most important seafood product of Thailand, which bring the large income to serve Thai economic. To promote shrimp agriculture, its growth has to be clearly understood. Shrimp growth is controlled by muscle regulatory genes via their signaling protein. To identify muscle growth related genes and study their functions, we achieved the molecular genetic techniques and bio-informatics tools. In particular, we identified an intriguing gene related to muscle regulation in abdominal muscle of pacific white shrimp, Litopenaeus vannamei, named LvProfilin. Its cDNA contains a coding sequence of 378 nucleotides. The deduced 125 amino acid exhibit 78 percent similarity with the shrimp Fenneropenaeus chinensis Profilin. The computed chemical formula of LvProfilin is C602H951N159O184S6. The 3 types of posttranslational modifications on LvProfilin were found including Acetylation, ADP-ribosylation and Phosphorylation. The secondary structure of LvProfilin protein was predicted. The seven x-helixs, three B-pleated sheets and eleven coils position were shown on LvDBP23 polypeptide. Additionally, the protein partners of LvProfilin were predicted. The result indicated that LvProfilin could bind with Actin protein as potential regulators of Actin filament dynamics that involving in muscle regulation. Other conjectured LvProfilin binding proteins include Tsr, Racl, Elongation factor 1 beta, Cappucino, Abl (Tyrosine-protein kinase) and SUMO. Interestingly, the RNA binding search showed a positive function of RNA binding. These preliminary results indicated that LvProfilin was likely to play an important role in muscle regulation in L. vannamei through its protein partners and control groups of RNA expression. Nevertheless, these predicted functions of LvProfilin need to be confirmed by laboratory assay to define its mechanism in the future.
Keywords: Bioinformatics; Muscle regulation; Binding protein; RNA Binding; Shrimp Profilin